Hubungan pengetahuan, pekerjaan ibu dan dukungan keluarga terhadap pemberian imunisasi lajutan pada anak usia 12-24 Bulan di Puskesmas Tanjung Api-Api Banyuasin II tahun 2024 - Elvira, Elvira; Afrika, Eka; Amalia, Rizki (NHM PRESS, 2024)
Immunization is an effort to actively increase a person's immunity against a disease. Follow-up immunization for toddlers under two years old (Baduta) (aged 18-24 months) is a repeat immunization to maintain the level of immunity and to extend the protection period of children who have received immunization. Not all children can receive further immunization, this can be seen from global vaccination data in 2021, it is known that 25 million children did not receive vaccinations, 2 million more than in 2020 and 6 million more than in 2019. The aim of this research is to find out the relationship between knowledge, maternal employment and family support simultaneously in providing follow-up immunizations to children aged 12-24 months at the Tanjung Api-Api Banyuasin II Community Health Center in 2024. Type and Design of Research is quantitative using analytical survey methods with a cross sectional approach. The population in this study were mothers with babies aged 18-24 months who visited the Tanjung Api-Api Community Health Center, totaling 60 people. The sample used was 60 respondents. The results of univariate analysis obtained from 60 respondents, there were 43 respondents (71.7%) who provided follow-up immunization and 17 respondents (28.3%) who did not. The results of the chi-square statistical test showed that the mother's knowledge variable was ρ value = 0.011, the family support variable was ρ value = 0.002 and the mother's employment variable was ρ value = 0.019, which was smaller than α=0.05, indicating that there was a significant relationship between knowledge and family support. and maternal work by providing follow-up immunizations to children aged 12-24 months at the Tanjung Api-Api Banyuasin II Community Health Center in 2024.